Antioxidant and Antimalarial Activity of Leea indica leaf extract against Malaria-mice Model - Erma Sulistyaningsiha , b, Talitha Yuni Amaliaa, Rizka Kartikasaria (Journal of Applied Pharmaceutical Science, 2017)
The increasing report on antimalarial resistance leads to the development of alternative drug from many resources. Leea indica is a medicinal plant traditionally used as an anti-malariaal agent in Indonesia. In this study we assessed the antioxidant as well as the antimalarial activity of L. indica. L. indica leaves were extracted in three different solvents (n-hexane, ethyl acetate, and methanol) and assessed for total phenolic, flavonoid and antioxidant activity. The antimalarial activity has been evaluated in malaria-mice model using the suppresive antimalarial assay. The highest fraction of total phenolic as well as total flavonoid was resulted from methanolic extract. It also demonstrated the strongest antioxidant activity with the IC50 of DPPH scavenging effect 1.62 + 0.02 ïg GAE/ml and the highest percentage of inhibition for hydroxyl radical, 57.60 + 2.52 %. Treatment with methanolic extract of L. indica 50, 100 and 200 mg/kg BW in malaria-mice models significantly (P < 0.05) decreased the MDA and increased the SOD level. The methanolic extract decreased parasitaemia level by 3.50 + 1.26 % on the day fourth and yielded 24.85 + 1.28 % of suppression. The L. indica leaf extract showed an antioxidant activity and could be considered as an antimalarial agent.
Keywords: Antimalarial, antioxidant, Leea indica, malaria-mice model.